2008
DOI: 10.1148/radiol.2492071870
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal Measurements of T1ρand T2 at MR Imaging in Healthy Subjects and Patients with Osteoarthritis

Abstract: Meniscal T1(rho) and T2 values correlate with clinical findings of OA and can be used to differentiate healthy subjects from patients with mild or severe OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
225
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(250 citation statements)
references
References 41 publications
22
225
3
Order By: Relevance
“…The TSLs used for the fitting were matched for the two studies as closely as possible, ie, T 1q (TSL 0, 10, 40, and 80 ms for young group; TSL 0, 12, 40, and 80 ms for remaining subjects). However, for meniscus, only the first three of the mentioned four TSLs for T 1q -weighted images were used [44]. T 1q -weighted images with the longest TSL had a very low signal-to-noise ratio (\ 5) for meniscus resulting from short T 1q in meniscus, respectively, and therefore were not used during map reconstruction.…”
Section: Quantitative Mri Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The TSLs used for the fitting were matched for the two studies as closely as possible, ie, T 1q (TSL 0, 10, 40, and 80 ms for young group; TSL 0, 12, 40, and 80 ms for remaining subjects). However, for meniscus, only the first three of the mentioned four TSLs for T 1q -weighted images were used [44]. T 1q -weighted images with the longest TSL had a very low signal-to-noise ratio (\ 5) for meniscus resulting from short T 1q in meniscus, respectively, and therefore were not used during map reconstruction.…”
Section: Quantitative Mri Analysesmentioning
confidence: 99%
“…Quantitative MRI techniques, however, including T 1q relaxation time mapping, enable the assessment of cartilage composition noninvasively and are useful to visualize the loss of collagen matrix that occurs early in the OA disease process [1,33,44,45]. An increase in T 1q relaxation times indicates loss of proteoglycans and possibly a concomitant increase in hydration [1,33,34,38].…”
Section: Introductionmentioning
confidence: 99%
“…A significant thrust in much of the qMRI literature is towards the correlation of various qMRI values to biochemical content, typically determined in explants through histology [14,26 -30,41,42,50-52,107], and to pain score or OA grade [39,43,44,48,54,56,57,90,126]. A number of groups have applied qMRI techniques to evaluate the differences between cartilage in normal subjects and patients with higher OA risk [43 -45,87,101].…”
Section: Shifting the Paradigm Towards Diagnosis Of Osteoarthritis Inmentioning
confidence: 99%
“…1,[5][6][7][8][9][10][11][12][13][14][15][16][17] Correlation has been reported between changes in PG content and the T 1 r relaxation time in vitro, 6,9 and in vivo studies have shown the utility of T 1 r mapping for PG changes in articular cartilage, especially for patients with osteoarthritis. [5][6][7]9,12,[13][14][15] However, accurate assessment takes a relatively long time because it requires scan- ning of 4 or 5 diŠerent T 1 r-prepared images with diŠerent times of spin-lock pulse (TSLs), [5][6][7]9,[12][13][14][15] and performance of T 1 r mapping would be preferable with a shorter examination time. We hypothesized that we could shorten examination time by modifying the method for calculating the T 1 r relaxation time and undertook this study to assess the utility of our proposed simpliˆed calculation method, which uses a small number of diŠerent T 1 rprepared images with diŠerent TSLs than those of previous studies.…”
Section: Introductionmentioning
confidence: 98%
“…1,2 As well, MR imaging can be used to assess the biochemical properties of articular cartilage by quantitative imaging approaches, such as sodium MR imaging, delayed gadolinium-enhanced MR imaging of cartilage (dGEMRIC), magnetization transfer imaging, T 2 mapping, diŠusion-weighted imaging, and T 1 r mapping. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] These approaches have been used to allow histological analysis of cellular morphology, proteoglycan (PG) concentrations, collagenˆber size, and orientation of hyaline cartilage. Sodium MR imaging and dGEMRIC have been employed to quantify the changes in PG depletion in articular cartilage.…”
Section: Introductionmentioning
confidence: 99%